Os professores e os projetos nas escolas públicas estaduais paulistas: um trabalho possível? - Fernandes, Maria José da Silva [UNESP] (My University, 2011)
At the end of the 20th century and beginning of the 21st century, the public state schools of São Paulo were marked by many reformist measures which implied in changes on the forms of work organization in the classroom. Trying to contribute with the discussions about the implications of reformation on teaching work, I explore some data from an empiric research of qualitative basis carried out among teachers of the Cycle II of the Elementary and High School. The research made possible the recognition of the perception of thirty teachers about the reformist measures, especially, regarding the denominated work projects, subject of this article. The interpretation of data pointed to a process of collection and obligatoriness of the execution of projects on daily school life, justified by the resource transfer to schools and bonus payment to the teachers. It is noted, however, an ethic suffering by the teachers which assumed new tasks without changes on the work conditions, transforming the projects into labels or slang that were far from being satisfactorily carried out.

No final do século XX e início do século XXI, as escolas públicas estaduais paulistas foram marcadas por várias medidas reformistas que implicaram em alterações nas formas de organização do trabalho na sala de aula. Procurando contribuir com as discussões sobre as implicações das reformas no trabalho docente, exploro alguns dados de uma pesquisa empírica de base qualitativa realizada com professores do Ciclo II do Ensino Fundamental e Ensino Médio. A pesquisa possibilitou o reconhecimento da percepção de trinta professores acerca das medidas reformistas, especialmente em relação aos denominados projetos de trabalho, objeto deste artigo. A interpretação dos dados apontou para um processo de cobrança e obrigatoriedade da realização de projetos no cotidiano escolar, justificados pelo repasse de recursos às escolas e do pagamento de bônus aos professores. Notouse, porém, um sofrimento ético por parte dos professores que assumiram novas tarefas sem que houvesse alterações nas condições de trabalho, transformando os projetos em rótulos ou jargões que estavam distante de serem satisfatoriamente realizados.
Teatchers and the ‘project” in São Paulo state public schools: a possible work?
Keywords: Projects; Teaching work; Educational reforms; Teaching-learning process; Projetos; Trabalho docente; Reformas educacionais; Processo ensinoaprendizagem